Dynamics of Trafficking in Human Beings and the Role of the Social Worker (Albanian Case) - Ervin, Muco (European Scientific Journal, ESJ, 2017)
The phenomena of Human Trafficking constitutes a violation of human rights, by restricting the freedom and putting in danger the lives of individuals, communities, and states. It positions individuals on slavery conditions and as a consequence victimizes them. Meanwhile, profits generated by human trafficking, the low risk and cost of engaging in this criminal activity, makes it very attractive for individuals, criminals networks, and the state as well. This causes negative consequences not only on individuals live but also on the economy and the political stability of a country. It harms social relation, brings a sense of fear and unsafety, and decreases the social trust among members of the community and state institutions. Moreover, THB has a negative impact on the economy by enabling individuals, organized crime, corporates, and states to maximise their profits by exploiting people. To succeed in the fight against THB and the reintegration process as well, we must recognize the factors that motivate and support it and actors involved in this operations (individuals, groups, organizations, and institutions). In this context, the role of the social worker is critical to understanding the phenomena and its consequences at different levels: micro, mezzo, and macro.